Implementasi Media Audio Lingual dalam Meningkatkan Maharah Istima’ Siswa Kelas XI IPA2 MA SA Darul Istiqomah Woro Kepohbaru - Fatya Nia Rahmawati (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2021)
Sometimes in some educational institutions they use handbooks in the learning process, but it is different in MA SA Darul istqamah, handbooks are only available for teachers. From this statement, the researcher concludes that the media has an important role in learning, so the researcher wants to know how the implementation of media, especially audio lingual media, in increasing maharah istima' at the institution.This study uses a qualitative research type using a descriptive approach. About the results of the study of the implementation of audio lingual media in increasing the special mahrah of class XI science students at MA SA Darul Istiqamah Woro Kepohbaru. In collecting the data, the researcher used observation and interview techniques, including interviews with the teacher in charge of the subject. And researchers used data analysis that was carried out continuously during the research process by reducing data, presenting data, and drawing conclusions.According to the observations that the researchers got, there are several kinds of media used in learning. Especially for istima' skills in Arabic the teacher gives an incomplete text, and later students are given the task of completing the text by listening to the audio that is played. Thus students can train especially in the ability to express words according to what is heard or commonly called maharah istima'.